Exchange Rates and Economic Growth During the Global Business Cycle: The Role of Labor Market Institutions - Vytautas Kuokštis; Muhammad Asali; Simonas Algirdas Spurga (Institute of Labor Economics (IZA), 2024)
The effect of exchange rate regimes on economic performance is one of the key questions in international economics, both academically and policy-wise. Based on the theory of Optimum Currency Areas (OCA), we examine how labor market regulations affect the relationship between exchange rate regimes and economic growth during global recessions and recoveries. Using a global panel dataset, we show that the negative influence of fixed exchange rate regimes during global shocks identified in earlier literature only manifests itself in countries with high labor market regulation. Conversely, fixers with less labor market regulation recover faster from global recessions than floaters.
Keywords: G01; G18; J08; O24; P17; 330; growth; labor market regulation; exchange rate regimes; global recessions; recovery